Studi Potensi Sumberdaya Peternakan di Kabupaten Mamberamo Raya - Sonbait, Lukas Yowel; Wambrauw, Yustina L. D. (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2019)
The objective of this research was to determine the potential resource of farms in Mamberamo Raya regency. The research was conducted in the Mamberamo Raya Regency between September and October 2012., A subjective approach of the qualitative method was used by interview and literature studies. The results showed that the livestock development in Mamberamo Raya regency had a promising future, but worth noting agribusiness channel from upstream to downstream. The problem faced by farmers was lack of venture capital, livestock, training, lack of access to education and short of affordable of quality health services, low investment both public and companies, lack of basic infrastructure such as roads, electricity, limited good river transport services, problem of land and sea linkages among districts and limited access to marketing. To optimize the efficiency of the production value and income of farmers then this should be supported by a cooperative storage facility or the expected distribution of the production can be accommodated and prepared collectively. Regional development of cattle and goats have good prospects in Mamberamo Hulu district, Central Mamberamo, Benuki, Roufaer, Mamberamo Lower and Upper Waropen. Other commodities need to be developed in all districts in Mamberamo are Pigs, Goats, range chicken and duck. Buffaloes also prospective by considering the potential freshwater swamps but the presence of natural predators such as estuarine crocodile and the annual flooding of Mamberamo should be considered. Livestock production is a priority at the moment in order to meet local consumption and improve animal protein sources.